1993
DOI: 10.1128/iai.61.6.2526-2531.1993
|View full text |Cite
|
Sign up to set email alerts
|

Piglet ileal mucus contains protein and glycolipid (galactosylceramide) receptors specific for Escherichia coli K88 fimbriae

Abstract: The aim of this study was to characterize the Escherichia coli K88-specific receptors in mucus from the small intestines of 35-day-old piglets with the isogenic strains E. coli K-12(pMKO05) (K88+) and E. coli K-12(pMK002) (K88-). These strains differed only in that the latter one cannot produce intact K88 fimbriae because of a deletion in the gene coding for the major fimbrial subunit. Adhesion was studied by incubating 3H-labeled bacteria with crude mucus, pronase-treated whole mucus, mucus fractionated by ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

1994
1994
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(34 citation statements)
references
References 34 publications
2
32
0
Order By: Relevance
“…The adhesion of radioactively labelled E. coli cells to the intestinal mucus from 14-day-old piglets was studied by using a modi¢cation of the methods [11,14,17,23]. All adhesion assays were performed in triplicate in multi-well polystyrene tissue culture plates (Linbro, £at bottom, 1.6 cm; Nunc, polysorp).…”
Section: In Vitro Adhesion Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…The adhesion of radioactively labelled E. coli cells to the intestinal mucus from 14-day-old piglets was studied by using a modi¢cation of the methods [11,14,17,23]. All adhesion assays were performed in triplicate in multi-well polystyrene tissue culture plates (Linbro, £at bottom, 1.6 cm; Nunc, polysorp).…”
Section: In Vitro Adhesion Assaymentioning
confidence: 99%
“…Metcalfe et al [12] and Willemsen and deGraaf [13] have demonstrated that the K88-speci¢c receptor in piglet intestinal mucus is a glycoprotein. Blomberg et al [14] later found that piglet ileal mucus contains protein and glycolipid receptors speci¢c for E. coli K88 ¢mbriae. The amount of K88ab receptor in the mucus was shown to be age related [10,12,13], as is susceptibility to E. coli K88 induced diarrhoea, and it was therefore proposed that the presence of receptors in mucus may play a role in the pathogenesis of K88-bearing strains [11,15].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the use of SPR to determine the interaction between adhesins and receptors on eukaryotic cells allows easy screening for blocking agents or receptor analogues to prevent infection. Indeed, one of the strategies to prevent ETEC-induced diarrhoea in both humans and animals, is to prevent attachment of the bacteria to their intestinal receptor and subsequent disease [20,[28][29][30][31][32][33][34].…”
Section: Resultsmentioning
confidence: 99%
“…The presence of both high-and low-a¤nity receptors for the K88 adhesin was ¢rst detected on adhesive brush borders by the use of kinetic binding studies [11]. Since then, putative K88 adhesin receptors have been identi¢ed in both intestinal brush border [12,13] and mucus [7,12,14] preparations. These putative receptors have been reported as being either glycoproteins [7,8,12,13] or glycolipids [14].…”
Section: Introductionmentioning
confidence: 99%